Streck, D., Redin, E., & Zitkoski, J. J. (org). (2008). Dicionário Paulo Freire. Belo Horizonte: Editora Autêntica. (Revista Lusófona de Educação, 2013)
Recensão crítica à obra de Danilo Streck e J.J. Zitkoski, Dicionário Paulo Freire.